Click Here: For Recommended Books for ICSE Self Study

Question 1: Evaluate

i)  \begin{bmatrix}  3 & 2    \end{bmatrix}   \begin{bmatrix}  2   \\ 0  \end{bmatrix}

ii)  \begin{bmatrix}  1 & -2    \end{bmatrix}   \begin{bmatrix}  -2 & 3  \\ -1 & 4  \end{bmatrix}

iii)  \begin{bmatrix}  6 & 4  \\ 3 & -1   \end{bmatrix}   \begin{bmatrix}  -1   \\ 3  \end{bmatrix}

iv)  \begin{bmatrix}  6 & 4  \\ 3 & -1   \end{bmatrix}   \begin{bmatrix}  -1  & 3  \end{bmatrix}

Answer:

i)  \begin{bmatrix}  3 & 2    \end{bmatrix}   \begin{bmatrix}  2   \\ 0  \end{bmatrix}  = \begin{bmatrix}  6    \end{bmatrix}

ii)  \begin{bmatrix}  1 & -2    \end{bmatrix}   \begin{bmatrix}  -2 & 3  \\ -1 & 4  \end{bmatrix} =  \begin{bmatrix}  0 & -5    \end{bmatrix}

iii)  \begin{bmatrix}  6 & 4  \\ 3 & -1   \end{bmatrix}   \begin{bmatrix}  -1   \\ 3  \end{bmatrix} = \begin{bmatrix}  6  \\ -6   \end{bmatrix}

iv)  \begin{bmatrix}  6 & 4  \\ 3 & -1   \end{bmatrix}   \begin{bmatrix}  -1  & 3  \end{bmatrix} : This multiplication is not possible as the number of columns in the first matrix is not equal to the number of rows in the second matrix.

\\

Question 2: If  A = \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix}, B = \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix} and I is a unit matrix of the order 2 \times 2 , find:

i) AB     ii) BA     iii) AI     iv) IB     v) A^2     vi) B^2A

Answer:

I = \begin{bmatrix}  1 & 0  \\ 0 & 1   \end{bmatrix}   

i) AB  = \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix}  \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix}  = \begin{bmatrix}  6 & 4  \\ -1 & -9   \end{bmatrix}

ii) BA = \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix}  \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix} = \begin{bmatrix}  -5 & 4  \\ 10 & 2   \end{bmatrix}

iii) AI = \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix}  \begin{bmatrix}  1 & 0  \\ 0 & 1   \end{bmatrix} = \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix}

iv) IB = \begin{bmatrix}  1 & 0  \\ 0 & 1   \end{bmatrix}  \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix}  = \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix}

v) A^2 = \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix} \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix}  = \begin{bmatrix}  10 & -4  \\ -10 & 14   \end{bmatrix}

vi) B^2A = \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix} \begin{bmatrix}  1 & -1  \\ 3 & 2   \end{bmatrix}  \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix} = \begin{bmatrix}  -2 & -3  \\ 9 & 1   \end{bmatrix} \begin{bmatrix}  0 & 2  \\ 5 & -2   \end{bmatrix} = \begin{bmatrix}  -15 & 2  \\ 5 & 16   \end{bmatrix} 

\\

Question 3: If  M = \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} , find M^2, \ M^3 \ and \ M^5 .

Answer:

M^2 = \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} = \begin{bmatrix}  5 & 0  \\ 0 & 5   \end{bmatrix}

 M^3  =  \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix} = \begin{bmatrix}  5 & 0  \\ 0 & 5   \end{bmatrix}   \begin{bmatrix}  2 & 1  \\ 1 & -2   \end{bmatrix}  = \begin{bmatrix}  10 & 5  \\ 5 & -10   \end{bmatrix}

M^5 = \begin{bmatrix}  5 & 0  \\ 0 & 5   \end{bmatrix}  \begin{bmatrix}  10 & 5  \\ 5 & -10   \end{bmatrix} = \begin{bmatrix}  50 & 25  \\ 25 & -50   \end{bmatrix}

\\

Question 4:  Find  x \ and \ y   if

i)    \begin{bmatrix}  4 & 3x  \\ x & -2   \end{bmatrix}   \begin{bmatrix}  5  \\ 1   \end{bmatrix} =  \begin{bmatrix}  y  \\ 8   \end{bmatrix}

ii)   \begin{bmatrix}  x & 0  \\ -3 & 1  \end{bmatrix}    \begin{bmatrix}  1 & 1  \\ 0 & y   \end{bmatrix} =  \begin{bmatrix}  2 & 2  \\ -3 & -2   \end{bmatrix} 

Answer:

i)    \begin{bmatrix}  4 & 3x  \\ x & -2   \end{bmatrix}   \begin{bmatrix}  5  \\ 1   \end{bmatrix} =  \begin{bmatrix}  y  \\ 8   \end{bmatrix} \Rightarrow \begin{bmatrix}  20+3x  \\ 5x-2   \end{bmatrix} = \begin{bmatrix}  y  \\ 8   \end{bmatrix} 

Therefore

  20+3x = y 

  5x-2=8 \Rightarrow x = 2 

Hence   y = 26 

ii)   \begin{bmatrix}  x & 0  \\ -3 & 1  \end{bmatrix}    \begin{bmatrix}  1 & 1  \\ 0 & y   \end{bmatrix} =  \begin{bmatrix}  2 & 2  \\ -3 & -2   \end{bmatrix} \Rightarrow \begin{bmatrix}  x & x  \\ -3 & -3+y  \end{bmatrix} =   \begin{bmatrix}  2 & 2  \\ -3 & -2   \end{bmatrix}  

Therefore

 x = 2   

 -3+y = - 2 \Rightarrow y = 1   

\\

Question 5: If  A =  \begin{bmatrix}  1 & 3  \\ 2 & 4  \end{bmatrix}, B =     \begin{bmatrix}  1 & 2  \\ 4 & 3   \end{bmatrix} \ and \ C =   \begin{bmatrix}  4 & 3  \\ 1 & 2   \end{bmatrix}  , find

i)  (AB) C      ii)  A (BC)      Is  A(BC) = (AB)C?  

Answer:

i)  (AB) C  = ( \begin{bmatrix}  1 & 3  \\ 2 & 4  \end{bmatrix}  \begin{bmatrix}  1 & 2  \\ 4 & 3   \end{bmatrix} )  \begin{bmatrix}  4 & 3  \\ 1 & 2   \end{bmatrix}

= \begin{bmatrix}  13 & 11  \\ 18 & 16  \end{bmatrix} \begin{bmatrix}  4 & 3  \\ 1 & 2   \end{bmatrix} = \begin{bmatrix}  63 & 61  \\ 88 & 86   \end{bmatrix}

ii)  A (BC)  =  \begin{bmatrix}  1 & 3  \\ 2 & 4  \end{bmatrix} ( \begin{bmatrix}  1 & 2  \\ 4 & 3   \end{bmatrix}   \begin{bmatrix}  4 & 3  \\ 1 & 2   \end{bmatrix} )

 = \begin{bmatrix}  1 & 3  \\ 2 & 4  \end{bmatrix} \begin{bmatrix}  6 & 7  \\ 19 & 18  \end{bmatrix} = \begin{bmatrix}  63 & 61  \\ 88 & 86   \end{bmatrix}

Is  A(BC) = (AB)C?   Yes.

\\

Question 6:  If  A =  \begin{bmatrix}  0 & 4 & 6  \\ 3 & 0 & -1 \end{bmatrix}, B =     \begin{bmatrix}  0 & -1  \\ -1 & 2 \\ -5 & -6  \end{bmatrix}   , calculate

i) AB       ii) BA       iii) A^2  

Answer:

i) AB =   \begin{bmatrix}  0 & 4 & 6  \\ 3 & 0 & -1 \end{bmatrix}  \begin{bmatrix}  0 & -1  \\ -1 & 2 \\ -5 & -6  \end{bmatrix}  = \begin{bmatrix}  -34 & -28  \\ 5 & 9   \end{bmatrix}  

ii) BA  =  \begin{bmatrix}  0 & -1  \\ -1 & 2 \\ -5 & -6  \end{bmatrix}  \begin{bmatrix}  0 & 4 & 6  \\ 3 & 0 & -1 \end{bmatrix} =   \begin{bmatrix}  3 & 0 & -1  \\ 6 & -4 & -8 \\ -18 & -20 & -24 \end{bmatrix}

iii) A^2  

This multiplication is not possible as the number of columns in the first matrix is not equal to the number of rows in the second matrix.

\\

Question 7: If  A =  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}, B =     \begin{bmatrix}  4 & 1  \\ -3 & -2   \end{bmatrix} \ and \ C =   \begin{bmatrix}  -3 & 2  \\ -1 & 4   \end{bmatrix}  . Find   A^2 + AC-5B   .     [2014]

Answer:

 A^2 + AC-5B  

 =   \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix} +  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}  \begin{bmatrix}  -3 & 2  \\ -1 & 4   \end{bmatrix} - 5 \begin{bmatrix}  4 & 1  \\ -3 & -2   \end{bmatrix} 

 =   \begin{bmatrix}  4 & 0  \\ 0 & 4  \end{bmatrix}  +  \begin{bmatrix}  -7 & 8  \\ 2 & -8  \end{bmatrix}   -  \begin{bmatrix}  20 & 5  \\ -15 & -10   \end{bmatrix}   =  \begin{bmatrix}  -23 & 3  \\ 17 & 14  \end{bmatrix}

\\

Question 8: If  M =  \begin{bmatrix}  1 & 2  \\ 1 & 1  \end{bmatrix} and I is the unit matrix of the same order as that of M; show that: M^2= 2M+3I

Answer:

I = \begin{bmatrix}  1 & 0  \\ 0 & 1   \end{bmatrix}   

M^2= 2M+3I

LHS = M^2 = \begin{bmatrix}  1 & 2  \\ 1 & 1  \end{bmatrix} \begin{bmatrix}  1 & 2  \\ 1 & 1  \end{bmatrix} = \begin{bmatrix}  5 & 4  \\ 4 & 5  \end{bmatrix}    

RHS = 2M+3I = 2 \begin{bmatrix}  1 & 2  \\ 1 & 1  \end{bmatrix} + 3  \begin{bmatrix}  1 & 0  \\ 0 & 1   \end{bmatrix} =  \begin{bmatrix}  5 & 4  \\ 4 & 5  \end{bmatrix}    

Hence proved LHS = RHS   

\\

Question 9: If  A =  \begin{bmatrix}  a & 0  \\ 0 & 2  \end{bmatrix}, B =     \begin{bmatrix}  0 & -b  \\ 1 & 0   \end{bmatrix} \ and \ M =   \begin{bmatrix}  1 & -1  \\ 1 & 1   \end{bmatrix}  and BA=M^2 , find the values of a \ and \ b .

Answer:

BA=M^2

\begin{bmatrix}  0 & -b  \\ 1 & 0   \end{bmatrix} \begin{bmatrix}  a & 0  \\ 0 & 2  \end{bmatrix} =\begin{bmatrix}  1 & -1  \\ 1 & 1   \end{bmatrix} \begin{bmatrix}  1 & -1  \\ 1 & 1   \end{bmatrix}  

\begin{bmatrix}  0 & -2b  \\ a & 0   \end{bmatrix} =  \begin{bmatrix}  0 & -2  \\ 2 & 0   \end{bmatrix}   

Therefore b = 1 \ and \ a = 2  

\\

Question 10:  If  A =  \begin{bmatrix}  4 & 3  \\ 2 & 1  \end{bmatrix}, B =     \begin{bmatrix}  1 & 0  \\ -2 & 1   \end{bmatrix} , find

i) A-B      ii) A^2      iii) AB      iv) A^2-Ab+2B 

Answer:

i) A-B =  \begin{bmatrix}  4 & 3  \\ 2 & 1  \end{bmatrix} - \begin{bmatrix}  1 & 0  \\ -2 & 1   \end{bmatrix} = \begin{bmatrix}  1 & 1  \\ 4 & 3  \end{bmatrix}

ii) A^2 =  \begin{bmatrix}  4 & 3  \\ 2 & 1  \end{bmatrix}  \begin{bmatrix}  4 & 3  \\ 2 & 1  \end{bmatrix} = \begin{bmatrix}  18 & 7  \\ 14 & 11  \end{bmatrix}

iii) AB =  \begin{bmatrix}  4 & 3  \\ 2 & 1  \end{bmatrix}  \begin{bmatrix}  1 & 0  \\ -2 & 1   \end{bmatrix} =  \begin{bmatrix}  2 & 1  \\ -4 & 3  \end{bmatrix}

iv) A^2-AB+2B 

 =  \begin{bmatrix}  18 & 7  \\ 14 & 11  \end{bmatrix} - \begin{bmatrix}  1 & 1  \\ 4 & 3  \end{bmatrix} +2 \begin{bmatrix}  1 & 0  \\ -2 & 1   \end{bmatrix}= \begin{bmatrix}  18 & 6  \\ 14 & 10   \end{bmatrix} 

\\

Question 11: If  A =  \begin{bmatrix}  1 & 4  \\ 1 & -1  \end{bmatrix}  and   B =  \begin{bmatrix}  1 & 2  \\ -1 & -1  \end{bmatrix}  find:

i)  (A+B)^2   ii)  A^2+B^2   iii) Is  (A+B)^2 = A^2+B^2

Answer:

i)  (A+B)^2

 = (\begin{bmatrix}  1 & 4  \\ 1 & -1  \end{bmatrix} + \begin{bmatrix}  1 & 2  \\ -1 & -1  \end{bmatrix} )^2

 = (\begin{bmatrix}  2 & 6  \\ 0 & -4  \end{bmatrix})^2

 = \begin{bmatrix}  2 & 6  \\ 0 & -4  \end{bmatrix} \times \begin{bmatrix}  2 & 6  \\ 0 & -4  \end{bmatrix}

 = \begin{bmatrix}  4 & -12  \\ 0 & 16  \end{bmatrix}

ii)  A^2+B^2

 = \begin{bmatrix}  1 & 4  \\ 1 & -1  \end{bmatrix} \times \begin{bmatrix}  1 & 4  \\ 1 & -1  \end{bmatrix} + \begin{bmatrix}  1 & 2  \\ -1 & -1  \end{bmatrix} \times  \begin{bmatrix}  1 & 2  \\ -1 & -1  \end{bmatrix}

 =  \begin{bmatrix}  5 & -8  \\ -2 & 13  \end{bmatrix} + \begin{bmatrix}  -1 & 0  \\ 0 & -1  \end{bmatrix}

  =  \begin{bmatrix}  4 & -8  \\ -2 & 12  \end{bmatrix}

iii) s  (A+B)^2 = A^2+B^2 : No

\\

Question 13: If  A =  \begin{bmatrix}  -1 & 1  \\ a & b  \end{bmatrix}  and   A^2=I , find   a \ and \ b .

Answer:

Given  I =  \begin{bmatrix}  -1 & 0  \\ 0 & 1  \end{bmatrix} 

Therefore

\begin{bmatrix}  -1 & 1  \\ a & b  \end{bmatrix} \times  \begin{bmatrix}  -1 & 1  \\ a & b  \end{bmatrix} =  \begin{bmatrix}  -1 & 0  \\ 0 & 1  \end{bmatrix} 

 \begin{bmatrix} 1+a & -1+b  \\ -a+ab & a+b^2  \end{bmatrix} =  \begin{bmatrix}  -1 & 0  \\ 0 & 1  \end{bmatrix} 

 \Rightarrow 1+a = a \Rightarrow a = 0 

Similarly -1+b=0 \Rightarrow b =1 

\\

Question 14:  If   A = \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix},  B = \begin{bmatrix}  2 & 3 \\ 4 & 1  \end{bmatrix},  \ and \ C = \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix} , then show that

i) A(B+C) = AB + AC    ii) (B-A)C=BC-AC 

Answer:

i) A(B+C) = AB + AC

LHS   = A(B+C) = \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix} (\begin{bmatrix}  2 & 3 \\ 4 & 1  \end{bmatrix} + \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix})  

= \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix} (\begin{bmatrix}  3 & 7 \\ 4 & 3  \end{bmatrix}) 

= \begin{bmatrix}  10 & 17  \\ 0 & 0  \end{bmatrix} 

RHS   = AB + AC  

= \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix} . \begin{bmatrix}  2 & 3 \\ 4 & 1  \end{bmatrix} + \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix}. \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix}  

= \begin{bmatrix}  8 & 7 \\ 0 & 0  \end{bmatrix} + \begin{bmatrix}  2 & 10  \\ 0 & 0  \end{bmatrix} 

= \begin{bmatrix}  10 & 17  \\ 0 & 0  \end{bmatrix} 

Hence LHS = RHS

ii) (B-A)C=BC-AC 

LHS = (\begin{bmatrix}  2 & 3 \\ 4 & 1  \end{bmatrix}- \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix}). \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix} 

= \begin{bmatrix}  0 & 2 \\ 4 & 1  \end{bmatrix} . \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix} 

=\begin{bmatrix}  0 & 4  \\ 4 & 18  \end{bmatrix} 

RHS = BC-AC 

= \begin{bmatrix}  2 & 3 \\ 4 & 1  \end{bmatrix} . \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix} -  \begin{bmatrix}  2 & 1  \\ 0 & 0  \end{bmatrix} . \begin{bmatrix}  -1 & 4  \\ 0 & 2  \end{bmatrix} 

=  \begin{bmatrix}  2 & 14  \\ 4 & 18  \end{bmatrix} -  \begin{bmatrix}  2 & 10  \\ 0 & 0  \end{bmatrix} 

= \begin{bmatrix}  0 & 4  \\ 4 & 18  \end{bmatrix} 

\\

Question 15: If A = \begin{bmatrix}  1 & 4  \\ 2 & 1  \end{bmatrix}  B = \begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix}  , and C = \begin{bmatrix}  1 & 0  \\ 0 & 2  \end{bmatrix}  , find the value of A^2+BC  

Answer:

A^2+BC  

= \begin{bmatrix}  1 & 4  \\ 2 & 1  \end{bmatrix} . \begin{bmatrix}  1 & 4  \\ 2 & 1  \end{bmatrix} + \begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix}  . \begin{bmatrix}  1 & 0  \\ 0 & 2  \end{bmatrix}  

= \begin{bmatrix}  9 & 8  \\ 4 & 9  \end{bmatrix} + \begin{bmatrix}  -3 & 4  \\ 4 & 0  \end{bmatrix}  

= \begin{bmatrix}  6 & 12  \\ 8 & 9  \end{bmatrix}  

\\

Question 16: Solve for x \ and \ y

i) \begin{bmatrix}  2 & 5  \\ 5 & 2  \end{bmatrix} .  \begin{bmatrix}  x  \\ y  \end{bmatrix} =  \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

ii) \begin{bmatrix}  x+y & x-4   \end{bmatrix} . \begin{bmatrix}  -1 & -2  \\ 2 & 2  \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

iii) \begin{bmatrix}  -2 & 0  \\ 3 & 1  \end{bmatrix} .  \begin{bmatrix}  -1  \\ 2x  \end{bmatrix} +3 \begin{bmatrix}  -2  \\ 1  \end{bmatrix} = 2 \begin{bmatrix}  y  \\ 3  \end{bmatrix}      [2014]

Answer:

i) \begin{bmatrix}  2 & 5  \\ 5 & 2  \end{bmatrix} .  \begin{bmatrix}  x  \\ y  \end{bmatrix} =  \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

\Rightarrow \begin{bmatrix}  2x+5y & 5x+2y   \end{bmatrix} = \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

Therefore

2x+5y = -7  

5x+2y=14  

Solving the above two equations we get

x = 4   and y = -3  

ii) \begin{bmatrix}  x+y & x-4   \end{bmatrix} . \begin{bmatrix}  -1 & -2  \\ 2 & 2  \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

\Rightarrow \begin{bmatrix}  x-y-8 & -2y-8   \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

Therefore

x-y-8=-7 \Rightarrow x-y=1  

Also -2y-8=-11 \Rightarrow y = \frac{3}{2}  

Substituting we get x = \frac{3}{2}+1 = \frac{5}{2}  

iii) \begin{bmatrix}  -2 & 0  \\ 3 & 1  \end{bmatrix} .  \begin{bmatrix}  -1  \\ 2x  \end{bmatrix} +3 \begin{bmatrix}  -2  \\ 1  \end{bmatrix} = 2 \begin{bmatrix}  y  \\ 3  \end{bmatrix} 

\Rightarrow  \begin{bmatrix}  2  \\ -3+2x  \end{bmatrix}  + \begin{bmatrix}  -6  \\ 3  \end{bmatrix} = \begin{bmatrix}  2y  \\ 6  \end{bmatrix} 

 \begin{bmatrix}  -4  \\ 2x  \end{bmatrix} = \begin{bmatrix}  2y  \\ 6  \end{bmatrix} 

Therefore y = -2 and x = \frac{6}{2}=3 

\\

Question 17: Find  i) the order of matrix M ii) and find M

i) M \times \begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} = \begin{bmatrix}  1 & 2   \end{bmatrix} 

ii) \begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} \times M = \begin{bmatrix}  13 \\ 5   \end{bmatrix} 

Answer:

i) M \times \begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} = \begin{bmatrix}  1 & 2   \end{bmatrix} 

We know

M_{m \times n}   \times B_{m \times n} = C_{m \times n}  

or M_{m \times n}   \times B_{2 \times 2} = C_{1 \times 2}  

Hence m = 1 and n = 2  

Therefore the order of M \ is \  1 \times 2  

Let  \begin{bmatrix}  a & b    \end{bmatrix}  

Therefore

\begin{bmatrix}  a & b    \end{bmatrix} .  \begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} = \begin{bmatrix}  1 & 2   \end{bmatrix} 

Or  \begin{bmatrix}  a & a+2b    \end{bmatrix} = \begin{bmatrix}  1 & 2   \end{bmatrix} 

Hence a = 1 \ and \  b =\frac{1}{2} 

Therefore M = \begin{bmatrix}  1 & \frac{1}{2}  \end{bmatrix} 

ii) \begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} \times M = \begin{bmatrix}  13 \\ 5   \end{bmatrix} 

We know

A_{m \times n}   \times M_{m \times n} = C_{m \times n}  

or A_{2 \times 2}   \times M_{m \times n} = C_{2 \times 1}  

Hence n = 2 and p = 1  

Therefore the order of M \ is \  2 \times 1  

Let  \begin{bmatrix}  a \\ b    \end{bmatrix}  

\begin{bmatrix}  1 & 1  \\ 0 & 2  \end{bmatrix} \times \begin{bmatrix}  a \\ b    \end{bmatrix} = \begin{bmatrix}  13 \\ 5   \end{bmatrix} 

\begin{bmatrix}  a+4b \\ 2a+b   \end{bmatrix}  = \begin{bmatrix}  13 \\ 5   \end{bmatrix}  

Therefore

a+4b = 13 

2a+b = 5 

Solving the above two equations

a =1 \ and \ b = 3 

\\

Question 18: If  A = \begin{bmatrix}  2 & x \\ 0 & 1  \end{bmatrix}  and B = \begin{bmatrix}  4 & 36  \\ 0 & 1  \end{bmatrix}  ; find x given A^2=B 

Answer:

Given A^2=B 

Therefore

\begin{bmatrix}  2 & x \\ 0 & 1  \end{bmatrix} . \begin{bmatrix}  2 & x \\ 0 & 1  \end{bmatrix} =  \begin{bmatrix}  4 & 36  \\ 0 & 1  \end{bmatrix} 

\begin{bmatrix}  4 & 3x \\ 0 & 1  \end{bmatrix}=  \begin{bmatrix}  4 & 36  \\ 0 & 1  \end{bmatrix} 

\Rightarrow 3x = 36 \ or \ x = 12 

\\

Question 19: Find positive integers p \ and \ q    such that \begin{bmatrix}  2 & x   \end{bmatrix} . \begin{bmatrix}  p \\ q  \end{bmatrix} = \begin{bmatrix}  25   \end{bmatrix}  

Address:

\begin{bmatrix}  2 & x   \end{bmatrix} . \begin{bmatrix}  p \\ q  \end{bmatrix} = \begin{bmatrix}  25   \end{bmatrix}  

\begin{bmatrix}  p^2+q^2   \end{bmatrix}= \begin{bmatrix}  25   \end{bmatrix}  

p^2+q^2 = 25  

Hence the possible integer combinations are

(p = 3 \ and \ q = 4) or (p=4 \ and \ q=3)

\\

Question 20: If A \ and \  B  are any two 2 \times 2 matrices such that AB = BA = B and B is not a zero matrix, what can you say about A matrix?

Answer:

Let A = \begin{bmatrix}  a & b \\ c & d  \end{bmatrix}  and B = \begin{bmatrix}  p & q \\ r & s  \end{bmatrix} 

Given

\begin{bmatrix}  a & b \\ c & d  \end{bmatrix} . \begin{bmatrix}  p & q \\ r & s  \end{bmatrix}   = \begin{bmatrix}  p & q \\ r & s  \end{bmatrix}   

\begin{bmatrix}  ap+br & aq+bs \\ cp+dr & cq+ds  \end{bmatrix} = \begin{bmatrix}  p & q \\ r & s  \end{bmatrix}   

\Rightarrow 

ap+br=p 

aq+bs=q 

cp+dr=r 

cq+ds=s 

Solving we get a = 1, b = o, c= 0, \ and \  d=1 

Hence A = \begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix} 

\\

Advertisements